THE EFFECT OF INTEGRITY LEARNING UNDERSTANDING OF LEADERSHIP TRAINING PARTICIPANTS ON ANTI-CORRUPTION BEHAVIOR OF CIVIL SERVANTS IN THE SOUTH KALIMANTAN PROVINCIAL GOVERNMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this study was to analyze the effect of Integrity Learning Understanding on Leadership Training participants on the Anti-Corruption Behavior of Civil Servants in the South Kalimantan Provincial Government. This research uses a mixed method approach with quantitative research in the first stage followed by qualitative research. This type of research is explanatory quantified and exploration for qualitative. The location is carried out in the South Kalimantan Provincial Government. The population in this study were alumni of Leadership Training at the Regional Human Resources Development Agency of South Kalimantan Province from 2017 to 2020 by means of simple random sampling totaling 900 people. The sample in this study amounted to 281 people. Interview informants in this study were 57 people consisting of policy makers, widyaiswara, education and training alumni, mentors, peers, subordinates and the community. Quantitative analysis technique using simple linear regression with SPSS application. The results show that the understanding of integrity learning has a significant effect on the anti-corruption behavior of Civil Servants in the Province of South Kalimantan, which consists of 13 Regencies, Municipalities and the Regional Government of South Kalimantan with a value of 0.05. Understanding of integrity material affects anti-corruption behavior because it teaches conformity between words, orders, and behavior, forms a person and a leader who is trustworthy, honest, trustworthy, does not harm in policy making, as a benchmark for ASN professionalism, reflects religion, enlighten, provide direction on how to deal with challenges in the service. Aspects of supporting anti-corruption behavior are understanding the importance of integrity material on anti-corruption behavior, learning methods for integrity material that are interesting and easy to understand, as well as support from colleagues and satisfaction from the community.